Digital Payroll Accounting Information System and PPh 21 Compliance for Staple Food MSMEs in Wanaherang Traditional Market - Uswatun Khasanah; Tutty Nuryati; Vitra Yozi (Greenation International Journal of Economics and Accounting, 2026)
Payroll management is one of the main obligations of entrepreneurs as tax collectors (tax withholding system) based on Indonesian tax law, particularly in the context of Article 21 of the Income Tax Law (PPh). However, many Micro, Small, and Medium Enterprises (MSMEs) in Indonesia still rely on manual payroll systems accompanied by incomplete administrative records, resulting in inaccurate tax calculations and potential non-compliance with applicable tax regulations. This study aims to: (1) identify whether MSMEs in the study sample still use manual or digital payroll systems, and (2) assess the completeness of payroll administration documents required for accurate PPh Article 21 reporting. This study uses a descriptive qualitative method, using a structured questionnaire distributed to 30 MSMEs engaged in the staple food (sembako) trading sector at Wanaherang Market, Bogor Regency. A total of 20 questionnaires were returned and analyzed, with a response rate of 66.7%. The results show that the majority of respondents still rely on manual payroll methods with incomplete administrative documentation. The 20 MSME respondents, only 9 entities (45%) had complete payroll documentation across all seven assessed components: employee data, revenue components, insurance deductions, Article 21 Income Tax calculations, supporting data, tax reporting documents, and internal control systems. The weakest component was internal control (only 40% complete), followed by completeness of supporting data (55%). As a contribution, this study proposes a conceptual digital payroll accounting information system framework consisting of six integrated stages employee data input, automated tax calculation, document generation, system validation, multi-level approval, and payroll disbursement designed to improve compliance efficiency for MSMEs. This prototype is planned to be implemented through community service activities targeting MSMEs that have not yet adopted a digital payroll system.